Public Health Insurance, Labor Supply, and Employment Lock * - Garthwaite, Craig; Gross, Tal; Notowidigdo, Matthew J. (Quarterly Journal of Economics, 2014)
We study the effect of public health insurance on labor supply by exploiting a large public health insurance disenrollment. In 2005, approximately 170,000 Tennessee residents abruptly lost Medicaid coverage. Using both across- and within-state variation in exposure to the disenrollment, we estimate large increases in labor supply, primarily along the extensive margin. The increased employment is concentrated among individuals working at least 20 hours a week and receiving private, employer-provided health insurance. We explore the dynamic effects of the disenrollment and find an immediate increase in job search behavior and a steady rise in both employment and health insurance coverage following the disenrollment. Our results are consistent with a significant degree of “employment lock”—workers who are employed primarily to secure private health insurance coverage.